Impacts of message sensation value and message appeal on viewer responses to YouTube anti-bullying videos - Wen-Chi Wu; Meng-Jung Lee; Hsi-Ping Nieh (Scientific Reports)
Abstract This study explored the impact of message sensation value (MSV) and message appeal on viewers’ responses to anti-bullying videos on YouTube from various sources. Through quantitative content analysis, 1431 videos were coded by trained coders based on predefined coding schemes. The results revealed that anti-bullying videos employed relatively low MSV levels (mean = 4.33, score range: 0–15). Most videos utilized positive emotional appeal (70.6%), about half employed rational appeal (54.9% self-efficacy appeal, 49.1% response efficacy appeal), and less than half incorporated negative emotional appeal (45.1%). Significant variations were observed in MSV and message appeal across different sources. Videos by YouTubers, amateurs, and recreational channels exhibited higher MSV levels than those by governments, non-profit organizations, and news channels. Videos uploaded by YouTubers received the highest number of views, likes, and comments, higher than those uploaded by governments and other sources. Videos employing higher levels of MSV received significantly more views, while message appeal had no significant effects after sources, languages, and numbers of subscribers were considered. The findings suggest that combining YouTubers’ broad reach with the credibility of government sources may offer an optimal strategy for effectively delivering accurate anti-bullying messages to a broader audience.